2021
DOI: 10.1371/journal.pone.0250926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous ascorbic acid on seed germination and seedling salt-tolerance of alfalfa

Abstract: Alfalfa (Medicago sativa L.) is an important legume crop for forage, agriculture, and environment in the world. Ascorbic acid (AsA) plays positive roles in plants. However, its effects on germination and salt-tolerance of alfalfa are unknown. The effects of AsA applications on seed germination and seedling salt-tolerance of alfalfa were investigated. The results revealed that 0.1 and 1 mmol L-1 of exogenous AsA increased germination, amylase, and protease, as well as seedling length, fresh weight (FW), dry wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…One explanation is that since watered seedlings were larger, perhaps seedlings were more apt to survive drought. Several studies report either larger unstressed plants or accelerated germination/emergence due to AsA [ 22 , 23 , 26 , 30 ]. A second explanation is that the increased root DM or decreased shoot:root ratio allowed for AsA-preconditioned plants to access more water during drought [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that since watered seedlings were larger, perhaps seedlings were more apt to survive drought. Several studies report either larger unstressed plants or accelerated germination/emergence due to AsA [ 22 , 23 , 26 , 30 ]. A second explanation is that the increased root DM or decreased shoot:root ratio allowed for AsA-preconditioned plants to access more water during drought [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, sodium l -ascorbic acid 2-phosphate showed a decreasing accumulation with over seed stratification period from 12M to 30M. This compound has been reported to inhibits germination at higher concentration but promotes germination at lower concentration ( Chen et al., 2021 ; Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 93%
“…GSH and AsA are directly involved in ROS detoxification, and their contents are highly and positively correlated with germination percentage and vigor index in oat seeds. Previous studies have indicated both endogenous and exogenous GSH and AsA were participated in the regulation of seed vigor [ 4 , 12 , 57 ]. Exogenous GSH and AsA could effectively alleviate aging damage in oat seeds, by enhancing activities of antioxidant enzymes in the AsA-GSH cycle, cytochrome c oxidase, and mitochondrial malate dehydrogenase, and maintaining mitochondrial structures in embryonic cells [ 4 ].…”
Section: Discussionmentioning
confidence: 99%